Kalibrasi Multikamera Sebagai Acuan Perhitungan Rekonstruksi Pose Objek Virtual pada Seni Animasi Tiga Dimensi - Samuel Gandang Gunanto (Rekam: Jurnal Fotografi, Televisi, Animasi)
The development of computer vision technology has penetrated in the field ofanimation and game art. Production time which generally takes a long time can be shortened significantly so that the animation industry productivity increases. But the existence of this technology is still very rarely used because of the expensive equipment and at least a man who mastered. This research is intended as an initial stage of looking for an alternative design of this technology. A good camera calibration will be a key reference for the right model of 3-dimensional reconstruction poses. Calibration error factor in pixels reprojection in this research is still good, 0.12. Visual results in 3-dimensional reconstruction of the cube as a result of exposure to the performance of this system is also still looks good, although shifting as much as 4.54 cm due to the extraction point.